Analisis Perubahan Penggunaan Lahan di Kabupaten Cianjur - Astuty, Yulia Indri; Mardalena, Ayu; Wibowo, Adi (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2023)
Cianjur Regency is one of the regencies located in West Java Province that is vulnerable to disasters because it is passed by the Cimandiri fault. Furthermore, according to BPS the population of Cianjur districts during year 2013 – 2021 increased by around 12.64%. The increasing number of population may cause various problems, including that is related to the spatial problems and land use issues. Moreover, the vulnerability of natural disasters is highly related to the land use of the area. Hence, research regarding land use in Cianjur districts to seek the its relation with the vulnerability of natural disasters is needed. This study conducted a land use analysis using Landsat 8 satellite imagery for 2013 and 2022 in 6 sub-districts in Cianjur district. To obtain land use classification of study area, an unsupervised classification of Landsat imagery is conducted with using Iso class algorithms. There three classes of land use resulted, namely namely built-up land, high vegetation and low vegetation. The overall accuracy of the data from year 2013 is 82.67% with kappa index of 0.74. Moreover the overall accuracy of the data from year 2022 is 89.33% with kappa index of 0.84. Changes of land use can be seen when these two different year data are overlay. Overall, the main differences are increasing number of built-up area and high vegetation land use classification while the low vegetation shows a decreasing number. It is hoped that this research can contribute to policy makers in establishing decisions related to spatial planning for sustainable development in disaster-prone areas around Cianjur district.